THE EFFECT OF SSCS LEARNING MODEL WITH METAPHOR APPROACH ON MATHEMATICS PROBLEM SOLVING ABILITY IN REVIEW OF STUDENTS' LEARNING STYLES - Janah, Elfa Latifatul; Netriwati, Netriwati; Widyastuti, Rany (Universitas Tanjungpura, 2023)
This study aims to determine whether there is an effect of the SSCS learning model with a metaphorical approach and PBL learning on mathematical problem-solving abilities in terms of learning styles. This research is a type of Quasy Experiment Design. The population in this study were students of class VIII at SMP N 09 Tulang Bawang Tengah, the sampling method used a simple random sampling technique. The data in this study were collected using tests and questionnaires. Hypothesis testing using analysis of variance of two unequal cells with a significance level of 5%. The prerequisite tests in this study include the normality test and the homogeneity test using SPSS which were carried out before testing the hypothesis. The results of the analysis obtained that p-value (sig.) = 0.037 0.05 then H0 was rejected, p-value (sig.) = 0.035 0.05 then H_0 was rejected, p-value (sig.) = 0.732 0, 05 then H0 is accepted so that, the results of the analysis in this study are (1) there is an effect of the SSCS learning model with a metaphorical approach and PBL model learning on mathematical problem-solving abilities. (2) there is an effect of visual, audio, and kinesthetic learning styles on mathematical problem-solving abilities. (3) there is no interaction between learning model factors and learning styles on mathematical problem-solving abilities.